2016
DOI: 10.18692/1810-4800-2016-2-127-133
|View full text |Cite
|
Sign up to set email alerts
|

The use of ectoine nasal spray in combination therapy of allergic rhinitis, the possibilities of barrier monotherapy

Abstract: В представленном исследовании произведено изучение сравнительной эффективности применения препарата Аква Марис® Сенс в качестве монопрепарата при лечении аллергического ринита, а также его комбинации с интраназальными глюкокортикостероидами. Под наблюдением находилось 90 пациентов с диагнозом аллергический ринит, интермиттирующая форма. Применение данного спрея направлено на создание особой гидрофильной пленки на поверхности слизистой полости носа для предупреждения попадания на слизистую оболочку аллергенов и… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The study of Abdulkerimov et al was of particular interest to us as the combination of ectoine and INS showed the best treatment effect in difficult-to-treat patients with moderate-to-severe rhinitis symptoms. This trend was also observed for the most effective intranasal formulation (azelastine and fluticasone furoate) in patients with moderate-to-severe rhinitis who exhibited complete or near-complete symptom relief faster than those receiving either fluticasone furoate or azelastine alone [46].…”
Section: Combination Therapy With Ectoinesupporting
confidence: 54%
See 4 more Smart Citations
“…The study of Abdulkerimov et al was of particular interest to us as the combination of ectoine and INS showed the best treatment effect in difficult-to-treat patients with moderate-to-severe rhinitis symptoms. This trend was also observed for the most effective intranasal formulation (azelastine and fluticasone furoate) in patients with moderate-to-severe rhinitis who exhibited complete or near-complete symptom relief faster than those receiving either fluticasone furoate or azelastine alone [46].…”
Section: Combination Therapy With Ectoinesupporting
confidence: 54%
“…Only 3 of the selected studies applied a randomization [ 43 , 46 , 50 ], whereas 3 did not carry out randomization due to local regulatory restrictions [ 47 , 49 ]. Two studies were single-arm trials [ 44 , 45 ], and the remaining studies did not present any information regarding randomization.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations